Implementation of Quality Policy and Higher Education Governance at Universiti Teknologi Malaysia - Safiyah Riyantini; Rudy Hartono; Supriadi; Mukhtar Latif; M.Syahran Jailani (PT. Anagata Sembagi Education, 2026)
This study examines the implementation of quality policy and higher education governance at Universiti Teknologi Malaysia (UTM) and its impact on academic excellence and global recognition. Employing a qualitative case study approach, the research analyzes how quality management systems, governance structures, employability-oriented curricula, and innovation ecosystems are integrated at the institutional level. Data were collected through document analysis and semi-structured interviews, and analyzed using thematic analysis. The findings indicate that quality policy at UTM functions as a strategic and transformative instrument rather than a compliance-based mechanism. The alignment between quality policy, governance, work-integrated learning, and research-driven innovation has contributed to strong graduate employability outcomes and enhanced international recognition, including performance in global university rankings. The study highlights that UTM’s success is rooted in the coherence between institutional strategy, governance, and continuous quality improvement. The findings contribute to the literature on higher education governance by demonstrating how universities in emerging contexts can leverage integrated quality policies to achieve sustainable academic excellence and global competitiveness while remaining responsive to national and societal needs.